'Living' Inks for 3D Bioprinting. Issue 8 (August 2019) - Hsu, Leo; Jiang, Xiaocheng
Abstract : A critical aspect in bioprinting is the formulation of bioactive inks. A recent breakthrough in bioink design (Qian et al. Nano Lett. 2019; https://doi.org/10.1021/acs.nanolett.9b00066) enables the direct writing of catalytically active microorganisms with unprecedented cell loading, tunable structural properties, and long-term activity. This strategy will create possibilities for bottom-up design and integration of functional living systems.